Liver Anatomy and Cross-Sectional Imaging Techniques: A Practical Approach - Garde, Parul Samir; Bhute, Rahul Bhagwan (Journal of Gastrointestinal and Abdominal Radiology, 2023)
In the past decade or two, there has been a significant change in the epidemiology of liver diseases, such as rise in the incidence of nonalcoholic steatohepatitis, good control of viral load in hepatitis B and C related liver diseases, and revolutionary changes in the treatment of hepatocellular carcinoma. Hence, monitoring of these diseases warrants effective noninvasive imaging techniques. Besides, organ transplantation has evolved to play a major role in the treatment of chronic liver diseases and acute liver failures. With the advent of better technology and new imaging sequences in cross-sectional imaging, there has been a dramatic change in the arena of liver imaging. Knowledge of these imaging modalities and effective application of the existing and new imaging techniques is essential to meet these changing clinical needs. This article aims at revisiting the liver anatomy from a practical stand point and touches upon the key cross-sectional imaging techniques of computed tomography and magnetic resonance imaging with recent advances.
Keywords: anatomy; cross sectional; imaging; liver